Correlation and Path Analysis in Candidate Bread Wheat (Triticum aestivum) Lines Evaluated in Micro-Plot Test Trial (Biological Sciences - PJSIR, 2005)
Correlation and path analysis among yield and yield-associated traits of eight candidate bread wheat lines, including two check varieties, were studied during 2001-02. All the characters studied differed significantly from each other, except biological yield and harvest index. Positive genotypic and phenotypic correlation was estimated between plant height and biological yield. Plant height was negatively correlated with harvest index and grain yield, both at the genotypic and phenotypic levels. It was, however, non-significant at both levels. Significant and positive genotypic correlations were observed between biological yield with harvest index and grain yield. Path analysis showed that days to heading, days to maturity, and plant height had negative direct effect on grain yield, whereas biological yield and harvest index had a high and positive direct effect on grain yield. It may be concluded from the present studies that biological yield and harvest index may be considered as the best selection criteria in the selection of high yielding genotypes, at least from the standpoint of the evaluated set of genotypes.